18 Utilizing lean six sigma and quality improvement (QI) to increase diabetes self-management education referrals within the endocrinology clinic. (2nd December 2020) - Burks, Jessica; Kollipara, Usha; Mutz, Jacqueline; Fish, Jason; Lopez, Estefania Andrioaia; Abramowitz, Jessica; Drobycki, Nancy; Ali, Sadia
Abstract : Background: Diabetes self-management education (DSME) is the ongoing process of facilitating the knowledge, skill, and ability necessary for diabetes self-care. Despite evidence that DSME improves clinical outcomes, health status, and quality of life for persons with diabetes referrals to DSME continue to be low in our population. Objectives: To increase referrals to Diabetes Self-Management Education (DSME) program from 26% at baseline to at least 40% in 12 months in our Endocrinology Clinic. Methods: We utilized Six Sigma DMAIC (Define-Measure-Analyze-Improve-Control) methodology to problem solve and perform process improvement. We created a multi-functional team including clinic staff, providers and quality improvement personnel to assist in the design and development of the new processes. In define phase we generated a project charter and communication plan. During the measure phase we determined the baseline referral volume, completed a current state process map and completed measurement system analysis. During the analyze phase we brainstormed reasons for low referrals (root cause analysis) and analyzed referral volume for trends. During improve phase we finalized future state workflow, implemented pre-visit planning, standing medical orders for referrals and provided training to clinic staff and providers. We continued bi-weekly chart audits for appropriate referrals being placed for 12 months. Results: As of August 2020, we were able to meet our goal at 42% with 1, 813 referrals placed for DSME. Of these, 1, 086 patients completed their education sessions (figure 1 ). Conclusions: Quality improvement tools and methodologies can be successfully utilized to improve care for diabetes in clinical settings. We were able to create a process that has maintained success, even during the uncertain times of COVID-19. The processes created and put in place were sustainable and have allowed the staff to continue placing referrals during tele-health visits and patients completing DSME virtually.